Marketing communication strategy to promote the Lambayecan cultural identity in the students of the educational institution Nuestra Señora de la Asunción - Faya Arboleda, Ana Lucía (2018)
In the present investigation, the Marketing Communication Mix Strategy was carried out, with the objective of im-proving the Lambayecan Cultural Identity in the 3rd, 4th and 5th students of the Educational Institution "Our Lady of the Assumption" , promoting it through a documentary, showing its history, folklore, nature, gastronomy, etc. And as this tool provides the way to position, and quickly capture consumer of which are founded by Felix Lazarsfeld and Kotler. Likewise, this research will contribute to other research with similar scenarios, thus comparing the theories given by different authors mentioned above and other studies shown by researchers, on the other hand, it seeks to propose a marketing communication strategy to promote and improve the Identity Cultural Lambayecana. This re-search is of non-experimental design, of a descriptive-proactive type; the population was conformed by the students of 3rd, 4th and 5th of the Educational Institution Our Lady of the Assumption, and for the data collection the tech-nique of the survey was used, by means of the questionnaire instrument and knowledge test. Finally, the marketing communication strategy will help improve the Lambayecana Cultural Identity in the 3rd, 4th and 5th students of the Educational Institution Our Lady of the Assumption.